Laparoscopic Cholecystectomy for Acute Gallbladder Disease During Index Admission- 11 the Optimum Timing for Surgery - Siddique, Md Ibrahim; Rahman, Md Atiar; Sheikh, Md Shahadot Hossain; Murshed, Khander Manzoor; Mubin, Samia; Siddiqui, Muhammad Ali; Majumder, Krisna Rani (Journal of Surgical Sciences, 2013)
Background: Laparoscopic cholecystectomy, initially considered a contraindication for the treatment of acute gallbladder disease, is now being practiced for treating acute cholecystitis worldwide. The purpose of the study is to evaluate the outcome of laparoscopic procedure in the management of acute gallbladder disease during the index admission in terms of safety and feasibility, hospital stay and the rates of complications and conversion to open cholecystectomy. Methods: Between January 2009 to December 2011, 174 patients (103 female, 71 male) with median age 43.5 years (range 27-73 years) with the diagnosis of acute gallbladder disease underwent laparoscopic cholecystectomy. Diagnosis of acute cholecystitis was made from history, physical findings and ultrasound evidence of acute inflammatory changes. Results: Median time from onset of symptoms to surgery was 70 hours. Median operative time was 76.5 minutes. Conversion rate was 1.7%. Minor post-operative complications occurred in 13.5% cases of laparoscopic procedure, which did not require further intervention. Median post-operative hospital stay was 2.5 days and total length of hospital stay was median 4.4 days. There was no mortality. Conclusion: In expert hands laparoscopic cholecystectomy for acute gallbladder disease during the index admission is safe with better clinical results, shorter hospital stay and an acceptable conversion and complication rates with additional financial benefit to the patients. DOI: http://dx.doi.org/10.3329/jss.v16i1.14442 Journal of Surgical Sciences (2012) Vol. 16 (1) : 11-17